2011
DOI: 10.1016/j.cellsig.2010.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Rab11a and its binding partners regulate the recycling of the ß1-adrenergic receptor

Abstract: Abstractβ1-adrenergic receptors (β1-AR) are internalized in response to agonists and then recycle back for another round of signaling. The serine 312 to alanine mutant of the β1-AR (S312A) is internalized but does not recycle. We determined that WT β1-AR and S312A were internalized initially to an early sorting compartment because they colocalized by >70% with the early endosomal markers rab5a and early endosomal antigen-1 (EEA1). Subsequently, the WT β1-AR trafficked via rab4a-expressing sorting endosomes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Overexpression of the tail domain saturates the tail-domainbinding sites on interacting effector proteins, preventing cargo from interacting with intact myosin motors. Owing to the sensitivity of a proportion of Rab11a-enriched vesicles to actin depolymerization and the relationship between Rab11a and myosin Vb demonstrated in other cells (Lapierre et al, 2001;Volpicelli et al, 2002;Fan et al, 2004;Wakabayashi et al, 2005;Provance et al, 2008;Gardner et al, 2011), we hypothesized that expression of a myosin Vb tail construct alters the distribution or motility of Rab11a-enriched membranes in LGACs. When expressed alone, the mCherry-myosin Vb tail-enriched compartment was highly concentrated around the MTOCs in the subapical domain (Fig.…”
Section: Trafficking Of Rab11a-enriched Vesicles Involves the Mt Networkmentioning
confidence: 99%
“…Overexpression of the tail domain saturates the tail-domainbinding sites on interacting effector proteins, preventing cargo from interacting with intact myosin motors. Owing to the sensitivity of a proportion of Rab11a-enriched vesicles to actin depolymerization and the relationship between Rab11a and myosin Vb demonstrated in other cells (Lapierre et al, 2001;Volpicelli et al, 2002;Fan et al, 2004;Wakabayashi et al, 2005;Provance et al, 2008;Gardner et al, 2011), we hypothesized that expression of a myosin Vb tail construct alters the distribution or motility of Rab11a-enriched membranes in LGACs. When expressed alone, the mCherry-myosin Vb tail-enriched compartment was highly concentrated around the MTOCs in the subapical domain (Fig.…”
Section: Trafficking Of Rab11a-enriched Vesicles Involves the Mt Networkmentioning
confidence: 99%
“…In this regard, we speculate that trafficking of the ␤ 1 -AR with an active PDZ through early endosomes was distinct from that of the transferrin receptor (Tfr) because Tfr recycled by "bulk" sorting that was largely independent of specific cytoplasmic sequences (40). This concept was derived from co-localization studies that have shown early colocalization between the Tfr and ␤ 1 -or ␤ 2 -AR in Rab5a and EEA1-positive early endosomes, followed by divergent trafficking itineraries between the Tfr and these ␤-ARs in later time frames (34,36). In this view, ␤ 1 -and ␤ 2 -AR recycled in a sequence-regulated manner through specific cis-acting sequences present on the receptor's cytoplasmic surface.…”
Section: Discussionmentioning
confidence: 99%
“…We have determined the effect of prolonged agonist exposures on the fate of biotinylated WT ␤ 1 -AR and (S312A) ␤ 1 -AR in HEK-293 cells (36). These studies revealed that the recycling WT ␤ 1 -AR was not significantly degraded even after 6 h of continuous exposure to agonist, whereas the non-recycling (S312A) ␤ 1 -AR was markedly (Ͼ80%) degraded (36).…”
Section: Identification Of a Role For The P ϭ ϫ3 Residue In The Type mentioning
confidence: 99%
See 1 more Smart Citation
“…2 During the last decade, many studies described the involvement of Rab GTPases in the regulation of GPCR trafficking and signaling. Rab GTPases were shown to be key regulators of GPCR anterograde and retrograde transport (Rab1, Rab2, Rab6, and Rab8), [3][4][5][6] endocytosis (Rab5), [7][8][9][10][11] recycling (Rab4 and Rab11), [11][12][13][14][15][16][17][18][19] and degradation (Rab7). 20 We and others established that a direct interaction between a GPCR and a Rab GTPase appears to be necessary in the proper trafficking of the receptor.…”
Section: Gpcrs and The Regulation Of Rab Gtpasesmentioning
confidence: 99%